Elevated C-Reactive Protein in Alzheimer's Disease Without Depression in Older Adults: Findings From the Health and Retirement Study. Issue 4 (21st October 2021) - Natale, Ginny; Clouston, Sean A P; Smith, Dylan M
Abstract: We examined the association between differential diagnoses of major stroke and probable Alzheimer's disease (AD) and mixed AD on C-reactive protein (CRP) in older adults with and without depression. Secondary data analyses examined associations between blood-based measures of probable peripheral inflammation using CRP collected from dried blood spots in the Health and Retirement Study, a nationally representative sample of individuals aged 50 and older. A validated pattern-recognition algorithm was utilized to identify cognitive decline indicative of probable AD, mixed AD, and major stroke. Negative binomial regressions were utilized to model concentrations of serologic CRP. On average, participants ( N = 4 601) were 70 years old, female, and non-Hispanic White. Mixed AD participants had a 0.26 mg/dL increase in CRP compared to unimpaired participants, controlling for demographics, health behaviors, and comorbidities. Those with mixed AD had 2.14 times increased odds of having high CRP (odds ratio = 2.14 [1.19–3.85]). In analyses stratified by depression, adults with mixed AD and without depression had an additional 0.37 mg/dL increase in CRP ( SE = 0.06; p < .001) compared to unimpaired adults. Those with AD without depression had a 0.20 mg/dL increase in CRP ( SE = 0.07; p < .01). Age was not associated with increased CRP in nondepressed older adults. Depressed adults with major stroke had a −0.26 mg/dL decrease in CRP ( SE = 0.11; p = .02), controlling for hypertension, alcoholic drinks/beverages per week, and smoking status. Concentration modeling revealed that participants with major stroke, probable AD, and probable mixed AD without depression had significantly higher CRP concentrations when compared to unimpaired older adults.